Identification and Differential Abundance of Mitochondrial Genome Encoding Small RNAs (mitosRNA) in Breast Muscles of Modern Broilers and Unselected Chicken Breed - Bottje, Walter G.; Khatri, Bhuwan; Shouse, Stephanie A.; Seo, Dongwon; Mallmann, Barbara; Orlowski, Sara K.; Pan, Jeonghoon; Kong, Seongbae; Owens, Casey M.; Anthony, Nicholas B.; Kim, Jae K.; Kong, Byungwhi C. (Frontiers in Physiology, 2017)
Background: Although small non-coding RNAs are mostly encoded by the nuclear genome, thousands of small non-coding RNAs encoded by the mitochondrial genome, termed as mitosRNAs were recently reported in human, mouse and trout. In this study, we first identified chicken mitosRNAs in breast muscle using small RNA sequencing method and the differential abundance was analyzed between modern pedigree male (PeM) broilers (characterized by rapid growth and large muscle mass) and the foundational Barred Plymouth Rock (BPR) chickens (characterized by slow growth and small muscle mass). Methods: Small RNA sequencing was performed with total RNAs extracted from breast muscles of PeM and BPR (n = 6 per group) using the 1 × 50 bp single end read method of Illumina sequencing. Raw reads were processed by quality assessment, adapter trimming, and alignment to the chicken mitochondrial genome (GenBank Accession: X52392.1) using the NGen program. Further statistical analyses were performed using the JMP Genomics 8. Differentially expressed (DE) mitosRNAs between PeM and BPR were confirmed by quantitative PCR. Results: Totals of 183,416 unique small RNA sequences were identified as potential chicken mitosRNAs. After stringent filtering processes, 117 mitosRNAs showing >100 raw read counts were abundantly produced from all 37 mitochondrial genes (except D-loop region) and the length of mitosRNAs ranged from 22 to 46 nucleotides. Of those, abundance of 44 mitosRNAs were significantly altered in breast muscles of PeM compared to those of BPR: all mitosRNAs were higher in PeM breast except those produced from 16S-rRNA gene. Possibly, the higher mitosRNAs abundance in PeM breast may be due to a higher mitochondrial content compared to BPR. Our data demonstrate that in addition to 37 known mitochondrial genes, the mitochondrial genome also encodes abundant mitosRNAs, that may play an important regulatory role in muscle growth via mitochondrial gene expression control.